Evaluating the Accounting Treatment of Value-Added Tax (VAT) at PT. Aneka Ragam Eng - Abdullah, Mhd; Masyitah, Emi (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Tax compliance is the fulfillment of tax obligations carried out by taxpayers to fulfill their responsibilities to achieve state development goals. PT. Aneka Ragam Eng is a manufacturing company operating in the field of Engineering, Construction & Manufacturing which is located at Jl. Palembang No. 35, Ex. Downstream Clever. The purpose of this research is to find out the causes of problems in evaluating the accounting treatment of Value Added Tax (VAT), to find out the obstacles faced, and the efforts made by PT. Aneka Ragam Eng on the evaluation of the accounting treatment of VAT. This research approach uses a descriptive approach and uses qualitative methods. Data management resulting from this research uses the Nvivo application. The accounting treatment for VAT in the company is in accordance with the Tax Harmonization Law No. 7 of 2021. After carrying out calculations, it is known that in the 2022 period the company experienced an underpayment of SPT because the output VAT was greater than the input VAT, this was caused by customer delays in paying bills. Apart from that, purchasing small amounts of materials or raw materials is also an obstacle faced by companies. The efforts made by the company to minimize the problems that occur are by ensuring customers pay their bills and following up on customer bills.